A Longitudinal Study of Growth and Relation With Anemia and Iron Overload in Pediatric Patients With Transfusion-dependent Thalassemia. Issue 6 (August 2016) - Nokeaingtong, Kwannapas; Charoenkwan, Pimlak; Silvilairat, Suchaya; Saekho, Suwit; Pongprot, Yupada; Dejkhamron, Prapai
Abstract : Short stature is one of the most common endocrinopathies in transfusion-dependent thalassemia (TDT). This study aimed to determine the longitudinal pattern of growth in pediatric patients with TDT and study the relationship between growth and hemoglobin level, serum ferritin level/iron overload parameters, and other clinical factors. The interval height-for-age Z-scores (HAZ) of 50 patients with TDT, of a mean age of 13.3±2.8 years, were analyzed using linear mixed model analysis. Nineteen patients (38%) had short stature with HAZ⩽−2.0. The prevalence of short stature increased with age. The estimated mean HAZ decreased by 0.19 SD per year from the age of 5 years until approximately 14 years (95% confidence interval [CI], −0.22 to −0.16, P <0.001). Male sex (estimate, −0.28; 95% CI, −0.43 to −0.14; P <0.001), mean 3-year hemoglobin level ⩽8 g/dL (estimate, −0.36; 95% CI, −0.53 to −0.19; P <0.001), mean 3-year ferritin level ≥1800 ng/mL (estimate, −0.44; 95% CI, −0.59 to −0.29; P <0.001), and cardiac T2* ⩽20 ms (estimate, −1.05; 95% CI, −1.34 to −0.77; P <0.001) were significantly associated with short stature. In conclusion, short stature in patients with TDT is common and relates significantly with increasing age, male sex, hemoglobin level, and iron overload status.